The changes of activity of effector caspase cascade components in case of alimentary obesity in rats (Bangladesh Journal of Medical Science, 2017)
Objective: The prevalence of obesity is rising in a global fashion, placing this population at higher risk for type 2 diabetes mellitus and cardiovascular disease. Current strategies for treatment of obesity are largely unsuccessful over the long term, since weight loss, even when achieved initially, is often followed by weight regain. More knowledge about the molecular and cellular mechanisms governing adipose tissue accumulation is needed to develop more effective preventative and therapeutic approaches to obesity.Materials and Methods: This study was conducted to investigate the macro- and microelements contents in the blood of experimental animals and assess their influence on the level of apoptotic cell death of blood leukocyte suspension in case of alimentary obesity, which was modelled on male, non-liner, white rats of around 3 months. Annexin V binding assays were performed by flow cytometry, the atomic absorption spectrophotometer was used to quantify micro- and macro-element contents.Results and Discussion: It was established a significant increase in leptin concentration at almost the same level of adiponectin. Experimental obesity was characterized by 2.1 times increasing of Annex+ cells percentage, while the level of PI+ cells remained within the control values. It was established the increasing of total calcium level, which exceeded by approximately 25.0 % of the control data. The same trend was marked on changes of ionized calcium level (p